Analysis of the incidence of uterine fibroid in Yekaterinburg - O. Yu. Sevostyanova; M. V. Koval; T. V. Chumarnaya; S. R. Belomestnov; N. E. Sevostyanova; T. A. Oboskalova; O. D. Striganova (Опухоли женской репродуктивной системы)
Background. Uterine fibroid (UF) is a benign tumor of the myometrium and is considered as one of the criteria for the state of women’s reproductive health. Objective information about the incidence of UF in a modern megalopolis allows us to assess the level of health of the female population, characterize the availability and quality of medical care, and plan its development.Aim. To analyze the incidence and prevalence of UF according to the data of medical organizations in Yekaterinburg in 2016–2022.Materials and methods. An epidemiological study of the incidence and prevalence of the adult female population of the city of Yekaterinburg in 2016–2022 was conducted. For the analysis, we used Form No. 12 of the Federal Statistical Observation of Medical Organizations located in the city. The incidence rates were calculated for the average annual female population aged 18 years and over, expressed in 0/0000. Absolute growth (decrease), growth rate (decrease), growth rate (decrease), average growth rate (decrease) were studied. The long-term dynamics of the indicators was determined using the average growth rate.Results. The incidence of UF was 130.890/0000, and the prevalence was 735.800/0000 in 2016. During the pre-pandemic period, the indicators increased significantly in 2019 compared to the baseline year 2016 (р < 0.001). The incidence increased by 1.96 times, the prevalence – by 1.39 times. The indicators decreased to the level of 2016 during the pandemic of new coronavirus infection (2020–2022) (р >0.05).Conclusion. The obtained dynamics of incidence and prevalence of UF in the population of women in a modern megalopolis is considered as a criterion for the state of women’s health, accessibility and quality of preventive and planned medical care for gynecological patients. The results of the study are recommended for planning medical care for women and can form the basis for continuing epidemiological studies.